DEVELOPMENT OF THE METHOD OF CALCULATION OF CHILLERS WITH THE COMBINED-COOLED CONDENSER - Fot A.N.; Vasiliev V.K (Problems of the Regional Energetics, 2014)
Combined cooling of condenser ensures stabilization of the condensation pressure and significantly reduces the consumption of cooling water and electricity. Exisiting methods of calculus of condenseres are applicable for condensers with air or with water cooling and are not valid when designing a condenser with combined cooling. The economical and technical recommendations for calculus must be elaborated in dependence of part of the time of using water or air for condenser unit cooling throughout the year. The mathematical model describing the operation of all elements of the chiller, as well as their technical and economic performances has been elaborated. The model includes analysis of the chiller during the whole period of operation and determines what share of water and air for cooling of condenser is the best. The analysis takes into account the cost of cooling water, power, energy costs for transporting the cooling water, for compressor drive, as well as the capital and operating costs.